Exchange Rate Choices of Microstates - Imam, Patrick (IMF Working Papers; Working Paper ;, 2010)
In this paper we first explain why most microstates (countries with less than 2 million inhabitants) have gained independence only in the last 30 years. Despite the higher costs and risks microstates face, their ability to better accommodate local preferences combined with a more integrated world economy probably explains why the benefits of independence have risen. We explain why microstates at independence have chosen either dollarization, currency board arrangements, or fixed exchange rates rather than more flexible forms of exchange rate systems. We then, using the Geweke-Hajvassiliou-Keane multivariate normal simulator, model empirically the determinants of each of the different fixed exchange rate regimes in microstates and analyze the policy implications.